Comparison of Somatization, Somatoform Dissociation, Anxiety Sensitivity, Psychological Pain, and Self-Care Behaviors in Patients With and Without Dental Anxiety - Sabzeh Ara Langaroudi, Milad; Davari, Roksana; Hosseinzadeh, Maryam; Elmi, Simin (Iranian Journal of Neurodevelopmental Disorders, 2026)
Purpose: The present study aimed to compare somatization, somatoform dissociation, anxiety sensitivity, psychological pain, and self-care behaviors in patients with and without dental anxiety.Methods and Materials: The present study employed a causal-comparative design. The statistical population consisted of patients attending private dental clinics in Ramsar in 2025. A total of 60 individuals, including 30 patients with dental anxiety and 30 patients without dental anxiety, were selected through purposive sampling. Data collection instruments included the Dental Anxiety Inventory (DAI; Stouthard et al., 1993), Patient Health Questionnaire-15 (PHQ-15; Kroenke et al., 2002), Somatoform Dissociation Questionnaire-20 (SDQ-20; Nijenhuis et al., 1996), Anxiety Sensitivity Index (ASI; Taylor & Cox, 1998), Orbach & Mikulincer Mental Pain Questionnaire (OMMP; Orbach et al., 2003), and Self-Care Questionnaire (SCQ; Lowe & Owen, 1996). Data were analyzed using multivariate analysis of variance (MANOVA) with SPSS-24 software.Findings: The results of multivariate analysis of variance demonstrated significant differences between patients with and without dental anxiety in somatization, somatoform dissociation, anxiety sensitivity, psychological pain, and self-care behaviors (P < 0.001). Patients with dental anxiety showed significantly higher levels of somatization, somatoform dissociation, anxiety sensitivity, fear of cardiovascular-gastrointestinal symptoms, fear of respiratory symptoms, fear of publicly observable anxiety reactions, fear of cognitive dyscontrol, and psychological pain compared to patients without dental anxiety. In contrast, self-care behaviors were significantly lower among patients with dental anxiety.Conclusion: The findings suggest that dental anxiety is associated with heightened bodily symptom expression, dissociative bodily experiences, fear of anxiety-related sensations, and increased psychological pain, while simultaneously reducing adaptive self-care behaviors.